Family history identifies sporadic schizoaffective disorder as a subtype for genetic studies - van der Merwe, Nicolaas J. (S Afr J Psychiatr, 2020)
BACKGROUND: Schizophrenia is a heterogeneous disorder with strong genetic vulnerability. Family history of schizophrenia has been considered in genetic studies under several models. De novo genetic events seem to play a larger role in sporadic cases. AIM: This study used the familial–sporadic distinction with the aim of identifying a more homogeneous phenotype to delineate the genetic and clinical complexity of schizophrenia. SETTING: The study was conducted at Weskoppies Hospital, Pretoria, South Africa. METHODS: The study included 384 participants with schizophrenia or schizoaffective disorder from the Afrikaner founder population in South Africa who are considered comparable to Caucasian patients from the United States. A comprehensive data capturing sheet was completed. RESULTS: When schizophrenia and schizoaffective disorder diagnoses were considered jointly, we found no significant differences between the sporadic and the familial groups for age at disease onset, season of birth, comorbid diagnoses, clinical symptomatology, history of suicide or marital status. When the diagnoses were examined separately, however, the sporadic schizoaffective disorder, bipolar type, was found to have a significantly lower age at onset (mean 20.6 vs. 25.3 years). CONCLUSION: The sporadic schizoaffective disorder, bipolar type, forms a more homogeneous subgroup for genetic studies.